Energy Expenditure And Its Relation With Load Level Using (PLAYERTEKTEAM) During Matches for Iraqi Soccer Primer Referees - Alaa, Ameer; Sami, Faris (Journal of Physical Education, 2020)
The problem of the research lies in not having criteria or analytical study about load levels and how much energy referees spend during matches. In addition to that, soccer training programs for referees are not based on quantitive analysis according to match requirements but through observation instead. The research aimed at identifying the values of load levels variables and energy expenditure using PLYERTEKTEAM for primer soccer league. The researchers used the descriptive method on (30) mid field referees and analyzed (81) matched. The best test was selected for each referee. The results showed a correlation relation between load levels and energy expenditure.